Methods of enhancing the performance and security of web applications - Machulski, Tomasz; Nowakowski, Grzegorz; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2019)
. This article presents the methods of enhancing the performance and security of web applications. It also evaluates them and describes how to use them. The methods have been implemented in a test application. The article presents results of the research comparing state of the application before and after implementation of every listed method. Conclusions about impact of the methods of enhancing performance and security of web applications are based on the results of the research.